Networks and neighbourhoods: devotional practices and attitudes towards the Church in late medieval Bristol, 1400-1500 - Lewis, Esther (2020)
This thesis focuses on religious life and devotional attitudes in the fifteenth-century port town of Bristol. It does this through a study of the surviving testamentary evidence and from records of heresy trials concerning individuals from the town. It aims to give an account of the dynamics of religious life across the whole of the town, and will focus on how testators and dissenters engaged with the institutions of the Church there. This thesis has used quantitative research methods, most notably Network Analysis, and qualitative analysis of specific case studies. The thesis is divided into three chapters. The first chapter explores why testators left legacies to multiple parish churches in Bristol in their wills. This will challenge the notion that the parish contained the piety of the laity and that wills only show death-bed piety. The second chapter discusses how some testators were more engaged with extra-parochial institutions such as chapels, hospitals and friaries than with their parish churches. The third chapter considers religious dissent and lollardy in the late medieval town, and the relationship that people who could be described as ‘heterodox’ might have had with the more ‘orthodox’ population of Bristol. This thesis gives a view of piety in town that includes a consideration of the whole town, and in doing so argues for a diversity of religious experience in the century prior to the Reformation.